1998
DOI: 10.1093/gerona/53a.2.m147
|View full text |Cite
|
Sign up to set email alerts
|

The Relation Between Morbidity and Cognitive Performance in a Normal Aging Population

Abstract: Existing morbidity as a whole contributes only modestly (up to 3.5%) to total variance in cognitive function. However, some specific, relatively common diseases of the elderly, such as diabetes and chronic bronchitis, may aggravate the age-related decline in cognitive ability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
158
0
2

Year Published

2000
2000
2011
2011

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 187 publications
(163 citation statements)
references
References 19 publications
2
158
0
2
Order By: Relevance
“…These data were taken from the Maastricht Aging Study 18 which comprised several studies of the biomedical and psychological determinants of cognitive ageing. The core project was a large crosssectional study of 2000 healthy individuals aged 24-81 years who were followed up for 12 years with regard to health characteristics and neurocognitive status.…”
Section: Introductionmentioning
confidence: 99%
“…These data were taken from the Maastricht Aging Study 18 which comprised several studies of the biomedical and psychological determinants of cognitive ageing. The core project was a large crosssectional study of 2000 healthy individuals aged 24-81 years who were followed up for 12 years with regard to health characteristics and neurocognitive status.…”
Section: Introductionmentioning
confidence: 99%
“…The study population consisted of 1823 participants, aged 24-81 years at baseline, and comprised four demographically identical panels, each stratified for age, sex, and general ability level. A detailed description of the MAAS study design can be found elsewhere [12,14]. The present study was carried out in one single panel of the MAAS study, consisting of 470 participants at baseline, of whom 301 individuals participated in the 12-year reassessments.…”
Section: Design and Study Populationmentioning
confidence: 99%
“…Participants were tested in four independent panel studies that were comparable with respect to inclusion and stratification criteria. An extensive description of the subject recruitment and stratification procedures is provided elsewhere [14,15].…”
Section: Samplementioning
confidence: 99%